Serum sodium levels and related treatment‐emergent adverse events during eslicarbazepine acetate use in adults with epilepsy. (1st July 2019) - Wechsler, Robert T.; Radtke, Rodney A.; Smith, Michael; Vossler, David G.; Strom, Laura; Trinka, Eugen; Cheng, Hailong; Grinnell, Todd; Blum, David; Vieira, Mariana; Moreira, Joana; Rocha, Francisco
Abstract: Objective: To examine the frequency of hyponatremia and potentially related symptoms in clinical trials of eslicarbazepine acetate (ESL) in adults with focal‐ (partial‐) onset seizures. Methods: This post hoc, exploratory analysis included data from three controlled phase 3 trials of adjunctive ESL (400‐1200 mg once daily), two phase 3 trials of ESL monotherapy (1200‐1600 mg once daily), and their open‐label extension studies. Exploratory endpoints included clinical laboratory measurements of serum sodium concentrations ([Na + ]), incidences of hyponatremia‐related treatment‐emergent adverse events (TEAEs), and incidences of TEAEs that are potential symptoms of hyponatremia. Results: The controlled trials of adjunctive ESL and ESL monotherapy included 1447 (placebo, n = 426; ESL, n = 1021) and 365 (ESL, n = 365) patients, respectively; 639 and 274 patients continued onto uncontrolled, open‐label extensions. In the controlled and uncontrolled trials ≤3.3% of patients taking ESL had a minimum postdose [Na + ] measurement ≤125 mEq/L, <9% had a >10 mEq/L decrease in [Na + ] from baseline, <6% had a hyponatremia‐related TEAE, and <2% discontinued the controlled trials due to a hyponatremia‐related TEAE. Hyponatremia appeared to be more frequent in the monotherapy (vs adjunctive therapy) trials; in the controlled trials of adjunctive ESL and ESL monotherapy, incidence generally increased with increasing ESL dose. The majority of patients with an investigator‐reported TEAE of "hyponatremia" or "blood sodium decreased" did not have a corresponding laboratory [Na + ] measurement ≤125 mEq/L. Some symptoms potentially related to hyponatremia (including nausea and vomiting) were more frequent in patients with a minimum postdose [Na + ] measurement ≤125 mEq/L. Significance: Reductions in serum sodium concentrations and hyponatremia‐related TEAEs occurred in a small number of patients taking ESL. Suspected hyponatremia should be confirmed and monitored via [Na + ] measurements.